2015
DOI: 10.1093/hmg/ddv246
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of tau splicing is disrupted in stem cell-derived neurons from frontotemporal dementia patients with the 10 + 16 splice-site mutation in MAPT

Abstract: The alternative splicing of the tau gene, MAPT, generates six protein isoforms in the adult human central nervous system (CNS). Tau splicing is developmentally regulated and dysregulated in disease. Mutations in MAPT that alter tau splicing cause frontotemporal dementia (FTD) with tau pathology, providing evidence for a causal link between altered tau splicing and disease. The use of induced pluripotent stem cell (iPSC)-derived neurons has revolutionized the way we model neurological disease in vitro. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
151
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(164 citation statements)
references
References 48 publications
12
151
1
Order By: Relevance
“…The majority of MAPT mutations are missense mutations that cluster around the microtubule binding domain, suggesting that these mutations most likely perturb the ability of tau to bind to microtubules and cause neuronal dysfunction or even death. Several groups have reported the isolation of iPSC-derived neurons, including one with MAPT A152T mutation from a patient with progressive supranuclear palsy (PSP), one with MAPT N279K and MAPT V337M from FTDP-17 patients, and one with 10+16 splice site mutation in MAPT gene (Ehrlich et al, 2015; Fong et al, 2013; Sposito et al, 2015). The study by Fong and colleagues showed that MAPT A152T neurons exhibit distinct degenerative features, characterized by breaks, bends and bulges along neuronal processes and reduced neuronal survival (Fong et al, 2013).…”
Section: Induced Pluripotent Stem Cells (Ipscs) As Models For Alsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of MAPT mutations are missense mutations that cluster around the microtubule binding domain, suggesting that these mutations most likely perturb the ability of tau to bind to microtubules and cause neuronal dysfunction or even death. Several groups have reported the isolation of iPSC-derived neurons, including one with MAPT A152T mutation from a patient with progressive supranuclear palsy (PSP), one with MAPT N279K and MAPT V337M from FTDP-17 patients, and one with 10+16 splice site mutation in MAPT gene (Ehrlich et al, 2015; Fong et al, 2013; Sposito et al, 2015). The study by Fong and colleagues showed that MAPT A152T neurons exhibit distinct degenerative features, characterized by breaks, bends and bulges along neuronal processes and reduced neuronal survival (Fong et al, 2013).…”
Section: Induced Pluripotent Stem Cells (Ipscs) As Models For Alsmentioning
confidence: 99%
“…Finally, it is well-recognized that different isoforms of tau can be generated via alternative splicing. Using iPSCs from controls and two patients with 10+16 splice-site mutation in MAPT , Sposito and colleagues show that control iPSC-derived neurons express 3R tau only during the first 100 days in culture (Sposito et al, 2015). Interestingly, prolonged culturing of control neurons switches the tau expression from 3R tau to a diverse complement of tau isoforms.…”
Section: Induced Pluripotent Stem Cells (Ipscs) As Models For Alsmentioning
confidence: 99%
“…One of the challenges of replicating tauopathy in human iPSC-derived neurons is that wild-type human iPSC-derived neurons, despite longer differentiation (>100 days), do not fully express adult tau splicing isoforms 3941 . The presence of select FTD tau mutations enhances the expression of adult 4-repeat tau splicing isoforms 3941 .…”
Section: Testing Aβ Cascade Hypothesis In Human Neuronal Modelsmentioning
confidence: 99%
“…The presence of select FTD tau mutations enhances the expression of adult 4-repeat tau splicing isoforms 3941 . However, control wild-type neurons do not express adult tau isoforms in the same conditions 3941 . This clearly limits the recapitulation of human tauopathy, in which 4-repeat tau plays an important role, in human iPSC-derived neurons without FTD tau mutations.…”
Section: Testing Aβ Cascade Hypothesis In Human Neuronal Modelsmentioning
confidence: 99%
“…Our group and others have developed protocols to obtain specific subtypes of neurons from fibroblast direct reprogramming without passing through an induced pluripotent stem cell20212223242526. Direct reprogramming can represent an interesting alternative strategy for neuronal modeling2728 in particular for late-onset neurological diseases since hPSCs generate immature neurons that may need long time in culture to recapitulate the disease phenotype2930.…”
mentioning
confidence: 99%